Pernikahan Wanita Hamil di Luar Nikah: Tinjauan Hukum Islam dan Implementasinya di Kantor Urusan Agama (KUA) Kecamatan Medan Timur (Pusat Riset dan Inovasi Nasional, 2024)
The topic of marrying women who conceive before marriage continues to spark debate in Islamic law, with diverse viewpoints across Muslim communities. Lack of awareness about Islamic rules and governmental policies frequently results in unions that defy both sharia teachings and applicable laws. This piece explores Islamic fiqh opinions on the marriage of unmarried pregnant women and evaluates how this is applied in marriage services at the Religious Affairs Office in Medan Timur District. The study adopts a qualitative framework using juridical-normative and empirical methods. Data was obtained by reviewing fiqh literature, legal regulations, and conducting interviews with KUA officials. The research reveals that ulama hold differing views on the acceptability of marrying a woman pregnant due to adultery, especially concerning the marriage ceremony timing and the child's familial status. Practically, the Medan Timur KUA follows guidelines from the Islamic Law Compilation and state administrative norms, all while exercising prudence. This investigation is intended to provide clearer insights for the public and act as a benchmark for Islamic law professionals facing similar scenarios.